In Vivo Cigarette Smoke Exposure to Examine the Expression of Genes Involved in the Inflammatory Response in the Mouse Uterus. Issue 6 (25th June 2021) - Budani, Maria Cristina; Carletti, Erminia; Tiboni, Gian Mario
Abstract: Cigarette smoke may impair uterine function, but the underlying mechanisms are poorly characterized. In this article, we describe the methodology for whole‐body exposure to cigarette smoke together with assessment of the impact of this exposure on the expression of a panel of genes related to stress and toxicity pathways in mouse uteri using an in vivo model. C57BL/6 mice are whole‐body‐exposed to three cigarettes daily, 7 days/week, for 2 months using a specific rodent ventilator. Uteri are then collected and subjected to qRT‐PCR analysis using the Stress & Toxicity PathwayFinder RT 2 Profiler PCR Array (Qiagen). Cigarette smoke was found to be associated with an upregulation (≥2‐fold) of C‐reactive protein ( Crp ; 2.65‐fold, p ‐value = 0.02), growth arrest and DNA‐damage‐inducible45γ ( Gadd45γ ; 2.11‐fold, p ‐value = 0.04), interferon γ ( Ifnγ ; 2.05‐fold, p ‐value = 0.01), and interleukin1α ( Il1α ; 7.74‐fold, p ‐value = 0.003) and downregulation of matrix metallopeptidase‐9 ( Mmp9 ; −2.42‐fold, p ‐value = 0.01). The protocol used in this study may represent a new experimental model of mouse in vivo mainstream exposure to cigarette smoke. In addition, the resulting overexpression of pro‐inflammatory cytokines and genes involved in cell cycle proliferation, together with the downregulation of extracellular matrix metallopeptidases, may represent a toxicological response to cigarette smoke exposure, with potential repercussion for the processes of uterine remodeling and growth that are essential for uterine receptiveness. A recommendation to expand upon this research area is made. © 2021 Wiley Periodicals LLC.